Passport Service Innovation Through the "Jemput Bola Berbasis HAM" Program by Immigration Office Class 1 TPI Pekanbaru - Adni, Dita Fisdian; Abdillah, Satrio; Juliana, Septa (Kemudi, 2023)
Immigration Office Class 1 TPI Pekanbaru initiated several innovations in passport services, including the Jemput Bola Berbasis Hak Asasi Manusia program, abbreviated Jempol HAM. This innovation has been implemented since 2021. It aims to help vulnerable groups such as people with disabilities, older, and sick people process passports so that they do not need to visit the immigration office because officers will come to their homes. This research was carried out to measure the implementation of the Jempol HAM passport service innovation by the Immigration Office Class 1 TPI Pekanbaru. Rogers' innovation attributes are used as an analytical tool in answering the problems in this research, namely relative advantages, compatibility, complexity, trialability, and observability. The qualitative research method with case study research type is the method that will be used in this research. The research results show that the Jempol HAM passport service innovation has been implemented well and provides convenience for vulnerable communities. Rogers' five innovation attributes are included in implementing the Jempol HAM innovation. This can be seen from the perceived benefits regarding time efficiency and the needs of vulnerable groups in Pekanbaru City regarding immigration services.